Chaos analysis of Buck converter with non-singular fractional derivative. (March 2022) - Liao, Xiaozhong; Ran, Manjie; Yu, Donghui; Lin, Da; Yang, Ruocen
Highlights: This work firstly introduces non-singular fractional derivative in the chaos analysis of DC-DC converter. The time-domain model of the Buck converter using the Caputo–Fabrizio derivetive is established. The chaotic phenomena of the peak current mode Buck converter is investigated. The work concludes that the chaos phenomena of the Buck converter are suppressed due to the fractional-orders. Abstract: This paper presents a time-domain mathematical model of the Buck converter using the non-singular fractional derivative that was proposed by Caputo and Fabrizio. The time-domain waveforms of the output voltage and current of the converter in different orders are obtained, and the correctness of the time-domain model has been verified. On this basis, the discrete iterative mapping model of the fractional-order Buck converter in peak current mode is established. The chaotic behaviors of the system are studied by numerical simulations, and the bifurcation diagrams at different fractional orders are investigated. The analog circuit implementation of the fractional-order Buck converter is established, and the results obtained via circuit simulations are consistent with the results of numerical simulations, which effectively validate the accuracy of the previous theoretical analysis.